The Elephant Seal industry at South Georgia - Laws, R. M. (Polar Record, 1953)
South Georgia, one of the Dependencies of the Falkland Islands, lies in the South Atlantic Ocean between lats. 53° 50′ and 55° S. and longs. 35° 50′ and 38°15' W. The island is about 120 miles long from north-west to south-east and its greatest breadth is under thirty miles: it is heavily glacierized with an indented coastline and a backbone of high mountains rising to over 9000 ft.